Research hotspots and evolution trends of rural resilience in the perspective of biodiversity—Based on citeSpace’s visual analysis of bibliometrics - Yang, Yuchi (Frontiers in Environmental Science, 2022)
Strengthening the construction of rural resilience and improving the rural ecotope and biodiversity are of great significance to improving the governance’s abilities of rural areas to resist external disturbances and various crises. Based on the 1786 documents which are associated with the research topics collected in the “Web of Science” database from 1992 to 2022, this study uses the visualization analysis method of the “CiteSpace document” to focus on the rural resilience from the ecosystem perspective, sort out the hotspots of rural resilience construction research, and study and judge the future development tendencies. It pertinently put forward the research evolution trends of “bottom–up ecological restoration” and “top–down planning improvement.” The research results are beneficial to provide useful references and direction enlightenment for the sustainable research of rural resilience and the formulation of planning strategies from the perspectives of biodiversity.